Employee Relations Pada PT. Solusi Energy Nusantara - Nurlina Aulia Santika; Siska Yuningsih (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Every employee who works has the motivation within himself that is needed in a company, every employee who has high work motivation can maintain the work style of each individual to achieve common goals in a company. Every company, of course, has a different way of employee relations or employee relations to build relationships with its employees. An employee who works must have motivation within himself, because employees who have high work motivation can maintain the work style of each individual to achieve goals together in a company, PT. Solusi Energy Nusantara is a company engaged in the service industry that requires the ability of employees to serve customers so that each employee's performance in providing service to its customers is the key to the good name of a company and customer satisfaction is also determined by employees, as well as employee involvement in achieving company success goals. So to achieve this it is necessary to have a harmonious relationship between employees. The purpose of this study is to determine employee relations at PT. Nusantara Energy Solutions. This research method uses a descriptive qualitative approach and employs Employee Relations theory. As for in this study data collection by means of in-depth interviews. As for the results in the study resulted from how employee relations at PT. Solusi Energy Nusantara, both in terms of communication which is carried out using discussion forums and coordination meetings every month, motivation in teamwork activities also uses agile transformation, employee welfare that is obtained by each employee also makes employees more enthusiastic to continue to provide the best performance results for the company , there is a commitment in the contract given to employees to remain loyal to the company and employee involvement is also considered very important which is the key to the company's success.